Analysis Of Interest In Sharia Banking Students In The Use Of Bank Sharia Indonesia (BSI) Mobile Banking Services - Firda Aulia; Nadia Dwi Kartika (Assyarikah: Journal of Islamic Economic Business, 2023)
This research was conducted to determine the factors that influence the Islamic Banking Student Attention of Sultan Maulana Hasanuddin Banten State Islamic University to implement Bank Syariah Indonesia (BSI) Mobile Banking Services. This study used a quantitative approach with survey methods in the form of questionnaires and questionnaires which were distributed to students in the city of Serang. Data were collected and analyzed using descriptive and inferential statistical methods. From the results of this research it can be concluded: The application of Mobile Banking makes it easier for Islamic Banking Students to do business, Mobile Banking makes it more secure in doing business, Mobile Banking makes students take control in carrying out business via their cellular telephones, Mobile banking is able to save time, Mobile banking suits their wishes Students who want to simplify agile services. Even though behind the relief and benefits provided to the Mobile Banking Service, it is still known that Islamic Banking Students have not paid attention to using Mobile banking services because they have not mastered or do not understand the method of carrying out Mobile banking in their area and there is no Indonesian Sharia Bank (BSI), as a result they use technology products. digital services provided by other conventional banks. it is still known that Islamic Banking Students have not paid attention to using Mobile banking services because they have not mastered or do not understand the method of carrying out Mobile banking in their area and there is no Indonesian Sharia Bank (BSI), as a result they use technology products. digital services provided by other conventional banks. it is still known that Islamic Banking Students have not paid attention to using Mobile banking services because they have not mastered or do not understand the method of carrying out Mobile banking in their area and there is no Indonesian Sharia Bank (BSI), as a result they use technology products. digital services provided by other conventional banks.